2008
DOI: 10.1080/19390210802519713
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Turmeric Extract on the Pharmacokinetics of Nifedipine After a Single Oral Administration in Healthy Volunteers

Abstract: The effects of turmeric extracts on the pharmacokinetics of nifedipine were examined in 10 healthy volunteers. An open-label and randomized crossover study was performed at 2-week intervals. In the control experiment, after a 10 h overnight fast, 10 mg of nifedipine (Adalat® capsule) was administered orally and blood was collected at 0, 0.5, 1, 2, 3, 4, 5, 6, and 8 h. In the combination experiment, the volunteers were orally administered 10 mg of nifedipine together with six tablets containing concentrated tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…These two RCTs utilized one or two doses of precipitant herbal medicines and therefore could not reflect the true clinical circumstance of chronic dosing. Further RCTs are necessary to address whether the two herbs are not potent CYP3A4 inhibitors in vivo following longer-term pretreatment [68, 69]. …”
Section: Resultsmentioning
confidence: 99%
“…These two RCTs utilized one or two doses of precipitant herbal medicines and therefore could not reflect the true clinical circumstance of chronic dosing. Further RCTs are necessary to address whether the two herbs are not potent CYP3A4 inhibitors in vivo following longer-term pretreatment [68, 69]. …”
Section: Resultsmentioning
confidence: 99%
“…Turmeric and its formulations were reported to improve various conditions in healthy individuals, reducing their risk of developing chronic diseases. A diverse range of studies have reported the tolerability of turmeric and its formulations in humans. For instance, a single dose of a 10 g turmeric root extract formulation in aged individuals improved oxygenation and cerebral blood flow, which are associated with improving brain activity . In another study, taking 1500 mg/day of BCM-95 (turmeric oil-based curcumin formulation) for 12 months stabilized cognitive function in older adults when compared to a placebo, recipients of which showed reduced cognitive function over the same period .…”
Section: Clinical Trials Of Turmeric and Curcuminmentioning
confidence: 99%
“…148,149 There also needs to be an examination of potential drug interactions following curcuminoid administration, because both inhibitory and enhancing effects on drug efficacy in humans have been reported. 2,[150][151][152][153][154][155][156][157] As with any herbal supplement, an awareness of reports of adverse consumer responses is important. Recently, Belgium's Federal Agency for Food Chain Safety and Italy's National Institute of Health warned consumers to avoid specific turmeric-containing supplements associated with an outbreak of acute cholestatic hepatitis (https://www.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%